HUBUNGAN PELAYANAN DAN FASILITAS KESEHATAN DENGAN KEPUASAN PASIEN PADA PELAYANAN MANAJEMEN TERPADU BALITA SAKIT (MTBS) DI PUSKESMAS KARYA TANI KABUPATEN LAMPUNG TIMUR - M. Arifki Zainaro; Dewi Kusumaningsih; Karyanto Karyanto (Universitas Malahayati Lampung, 2019)
ABSTRACT : CORRELATION BETWEEN SERVICES AND HEALTH FACILITIES WITH PATIENT SATISFACTION ON INTEGRATED MANAGEMENT OF CHILDHOOD ILLNES (IMCI) SERVICE AT KARYA TANI’S PUBLIC HEALTH CENTER DISTRICT Background : The Purpose is on integrated management of childhood illnes (IMCI) significantly reduce the mortality and morbidity associated with the most common diseases in infants. Contribute to the growth and development of children's health. Achievement indicators of health care of children under five in 2016 amounted to 75.82% do not meet the Strategic Plan targets by 83%. The achievement of this indicator also decreased compared to 2015, which amounted to 70.12%.Purpose: To know correlation between service and health facility patien satisfaction on integrated management of childhood illnes (IMCI) At Karya Tani’s Public Health Center District East Lampung 2018Methods: Quantitative research type, analytic research design with cross sectional approach. The population is all mothers with toddlers who perform the examination with average visits per month as many as 63 people. The statistical test used was the statistical test Chi-Square.Results: Frequency distribution of patient satisfaction, with dissatisfied category as many as 34 respondents (54%). Distribution of service frequency, with less good category as many as 36 respondents (57.1%). Distribution of frequency of health facilities, with poor category as many as 25 respondents (39.7%).Conclusion : There is a correlation service with patient satisfaction Integrated Management of childhood Pain (IMCI). The results obtained (p-value 0.0001 α 0.05) with the value of OR 18,229. It is expected that Puskesmas Karya Tani can provide training on integrated management of childhood illnes (IMCI) to health workers as well as providing facilities and infrastructure especially for Integrated Management of Childhood (IMCI). Keyword : Service Health Facilities, Patient Satisfaction, IMCI